Dry Eye Syndrome Risks in Patients With Fibromyalgia: A National Retrospective Cohort Study. Issue 4 (January 2016) - Chen, Chao-Hsien; Yang, Tse-Yen; Lin, Cheng-Li; Chen, Chih-Sheng; Lin, Wei-Ming; Kuo, Chia-Nan; Lin, Ming-Chia; Kao, Chia-Hung
Abstract : Abstract: The coexistence of fibromyalgia (FM) and dry eye syndrome (DES) has been previously reported. However, there are few studies on how patients with FM may develop concomitant DES. Patients with chronic widespread pain, like FM, chronic fatigue syndrome, and irritable bowel syndrome (IBS), was concerned for the rheumatic or psychosomatic disorders which might adequately reflect the long-term risk of DES. We retrieved data on FM patients from the National Health Insurance Research Database of Taiwan covering the years 2000 to 2011. Our FM population consisted of 25, 777 patients versus 103, 108 patients in the non-FM group: the overall incidence of DES in these populations was 7.37/10, 000 and 4.81/10, 000, respectively. Male FM patients had a higher incidence of DES, with a 1.39-fold DES risk for males and a 1.45-fold for females after adjustment for confounding factor. Notably, FM patients aged ≤49 years had an elevated 80% risk of DES compared with the non-FM group. Without comorbidities, FM patients had an approximately 1.40-fold risk of DES than those without FM. The additive effects of FM and IBS or FM and sleep disturbance were pointed out that the risk for DES would be elevated when the FM patients with IBS or sleep disturbance. FM patients have a higher incidence of DES than that of non-FM patients. They carry long-term DES risks from a relatively young age, particularly those with psychiatric problems. Risk stratification for a timely psychiatric medication intervention and risk modifications are not intended.